The Implementation of Positive Reinforcement in Increasing the Learning Motivation of Broken Home Students at MIN Cirebon City - Siti Saniah; Adi Abdurahman (Indonesian Journal of Elementary Education (IJEE), 2024)
This study aims to find out how to apply positive reinforcement and describe the supporting and inhibiting factors in implementing positive reinforcement to increase the learning motivation of broken home students. The method used in this study is to use a qualitative descriptive approach with two types of data sources, namely primary data and secondary data. The data collection technique using observation was carried out to observe the learning process by applying positive reinforcement in the classroom, interviews were conducted to obtain the right information from trusted sources regarding the supporting factors and inhibitions of the implementation of positive reinforcement, and documentation was carried out to trace the data of broken home students in the form of documents and information that supported the research. The subjects in this study were 3 homeroom teachers and 7 broken home students. The data analysis techniques used are data reduction, data presentation, conclusion and verification. The results of the study show that the application of positive reinforcement in increasing the learning motivation of broken home students is quite significant by providing a positive sentence in the form of: the example you give is very precise. Showing gestures or facial expressions that give a good impression in the form of: smile, thumbs up, applause. Provide reinforcement through physical contact by shaking hands, patting the shoulders, and raising the students' hands when winning the competition. The supporting factors are always prioritizing cooperation with homeroom teachers, the existence of adequate facilities and infrastructure, students who have future aspirations and a desire to learn. And the inhibiting factor, because of the background of the broken home student and the different characteristics of each student.Keywords: Positif reinforcement, Motivation, Broken home